Case Study Integration in the Undergraduate Classroom: Can We Enhance Willingness to Communicate? - Jessica L Harsh; Alexa J Lamm; Katie Abrams; Courtney Meyers; Ricky Telg; Becky Raulerson (Journal of Applied Communications, 2018)
The agricultural and natural resources (ANR) industry faces many pressing issues involving animal health, biotechnology, climate change, food safety, food security, invasive species, marketing and trade, and water. Undergraduate students must be prepared and willing to communicate about these issues, which can often be complex and controversial when entering the ANR workforce. This study sought to determine if the integration of case studies influenced students’ self-perceived willingness to communicate about ANR issues while taking a communication course that teaches about ANR issues. A pre/posttest, experimental research design assessed students’ willingness to communicate about nine key ANR issues identified by the United States Department of Agriculture as challenge areas with case study integration used as the treatment. Using three undergraduate courses at three universities as the sample, a significant positive difference in willingness to communicate about all nine issues was found between the experimental and control groups. Based on these findings, it is recommended that case studies be integrated into classrooms when teaching about ANR issues. Future research should determine if this impact occurs when the case studies are used in undergraduate courses outside of the communication courses used as the foundation in this study, in other science-focused undergraduate and graduate courses, and in non-formal settings such as extension education programs.
Keywords: communication; experiential learning; agricultural issues education; case studies; undergraduate education